2011
DOI: 10.18043/ncm.72.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated With Use and Susceptibility to Use of Cigarettes Among North Carolina Adolescents: Results From the 2007 Statewide Survey of High School Students

Abstract: According to a 2005 nationwide survey, 28% of students had tried smoking before entering high school; by the last year of high school, 53% had tried smoking [2]. Smoking rates among students in grade 8 peaked in 1996, at approximately 22%, and smoking rates among students in grade 12 peaked the following year, at approximately 37% [2]. Nationally, while smoking rates among high school students began to decline in the mid-1990s, the rate of decline began to slow around 1999 [3]. The current rate for cigarette s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Chippers and daily smokers were more likely to believe smoking is cool compared to non-daily light smokers. Several studies among U.S. adolescents (Carpenter et al, 2009;Kandra et al, 2011) have shown a positive relationship between the perception that cigarette smoking is cool and current cigarette smoking status or smoking susceptibility. Perceptions of waterpipe smoking "coolness" have also been shown to be a predictor of current waterpipe use (Jordan and Delnevo, 2010).…”
Section: Psychosocial Characteristics Of Latent Classes Of Youth Smokersmentioning
confidence: 99%
“…Chippers and daily smokers were more likely to believe smoking is cool compared to non-daily light smokers. Several studies among U.S. adolescents (Carpenter et al, 2009;Kandra et al, 2011) have shown a positive relationship between the perception that cigarette smoking is cool and current cigarette smoking status or smoking susceptibility. Perceptions of waterpipe smoking "coolness" have also been shown to be a predictor of current waterpipe use (Jordan and Delnevo, 2010).…”
Section: Psychosocial Characteristics Of Latent Classes Of Youth Smokersmentioning
confidence: 99%